L'estetica di Hegel e la Bildung. Annotazioni - Giosi, Marco (Studi sulla Formazione/Open Journal of Education, 2012)
This article examines the topic related to the value and meaning of the Hegel’s aesthetics. In particular, looking at what are the educational and pedagogical implications regarding the education of man. In this sense, particular emphasis has the notion of Bildung, that just takes a crucial role in the aesthetic experience.